Subduction Dynamics at the Northwestern Pacific Slab Edge: Constraints of Tomography in Kamchatka - Yanting LIU; Chengcheng ZHONG; Guoming JIANG; Dapeng ZHAO (CT Lilun yu yingyong yanjiu, 2024)
Kamchatka is located at the northwestern edge of the Pacific plate. The Pacific slab is subducting into the mantle along the Kamchatka trench. Are there any differences in subduction features near the edge? To answer this question, seismic tomography was applied to 77,141 P-wave arrival times of 2239 local earthquakes and 75 teleseismic events recorded at 76 permanent stations to study the three-dimensional velocity structure to a depth of 700 km below Kamchatka. A clear high-velocity anomaly was evident beneath the study region, which is consistent with the distribution of intermediate-depth and deep-focus earthquakes. This high-velocity anomaly was interpreted as the subducting Pacific slab with its subduction angle and depth gradually increasing from the north to south along the Kamchatka trench. Another high-velocity anomaly appeared in the mantle transition zone and the uppermost lower mantle, which may reflect a piece of detached oceanic lithosphere due to melting of the subducting slab near the slab edge. Two slab windows were also found, through which hot mantle materials flowed from the subslab to the upper-mantle wedge. Large-scale low-velocity anomalies exist under the volcanic front, which reflect hot and wet upwelling flow in the mantle wedge due to the slab dehydration.